E-Value Creation Model and Social Media Marketing in Improving E-Reputation of The Perfume Refill Industry - Hernandi Sujono (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The company's reputation is one of the most valuable, essential, strategic, and enduring intangible assets a company owned. Reputation is an asset that allows a company to differentiate itself and even allow consumers to pay a premium for products with an exclusive character. This study aims to determine the influence of the E-Value Creation Model and Social Media Marketing in Increasing the E-Reputation of the Perfume Refill Industry. Descriptive quantitative research includes in this study. This study focused on the Malang City refill perfume industry and employed random sampling as a sampling method. As a result, the sample for the study consisted of 159 refill perfume businesses. The data analysis technique in this study used Partial Least Square (PLS). PLS is a structural equation model modeling (SEM) approach based on variance or component-based structural equation modeling. The results showed that E-Value Creation and Social Media Marketing significantly positively influence E-reputation.